2023
DOI: 10.1186/s12912-023-01209-9
|View full text |Cite
|
Sign up to set email alerts
|

Workflow interruption and nurses’ mental workload in electronic health record tasks: An observational study

Abstract: Background Workflow interruptions are common in modern work systems. Electronic health record (EHR) tasks are typical tasks involving human–machine interactions in nursing care, but few studies have examined interruptions and nurses’ mental workload in the tasks. Therefore, this study aims to investigate how frequent interruptions and multilevel factors affect nurses’ mental workload and performance in EHR tasks. Methods A prospective observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The total time was calculated when the nurse created the patient profile in several small steps. Nurses’ EMR tasks are sometimes interrupted by other priority events, leading to task switching [ 17 ]. If a nurse was in the middle of entering the patient profile and left without saving it or logging out, the input time may have been overestimated.…”
Section: Methodsmentioning
confidence: 99%
“…The total time was calculated when the nurse created the patient profile in several small steps. Nurses’ EMR tasks are sometimes interrupted by other priority events, leading to task switching [ 17 ]. If a nurse was in the middle of entering the patient profile and left without saving it or logging out, the input time may have been overestimated.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Shan et al explored the rationale for the effects on mental workload and performance after task interruptions. The results showed that the interruption of this task was prone to cause negative emotions 12 . Negative emotion plays a mediating role in the path between task performance and mental workload, which may lead to the increase of mental workload.…”
Section: Backgroundsmentioning
confidence: 95%
“…Currently, most related studies have examined the negative aspects of interruptions [ 4 , 5 ]. Surgical counting interruptions may result in prolonged operating time, reduced risk detection capabilities, and increased mental workload [ 6 8 ]. Therefore, measures should be taken to respond to interruptions, which should be managed according to source, attributes, outcomes and responses.…”
Section: Introductionmentioning
confidence: 99%